2009
DOI: 10.1002/art.24304
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of cartilage degeneration in a rat model of osteoarthritis by intraarticular treatment with recombinant lubricin

Abstract: Objective. Lubricin, also referred to as superficial zone protein and PRG4, is a synovial glycoprotein that supplies a friction-resistant, antiadhesive coating to the surfaces of articular cartilage, thereby protecting against arthritis-associated tissue wear and degradation. This study was undertaken to generate and characterize a novel recombinant lubricin protein construct, LUB:1, and to evaluate its therapeutic efficacy following intraarticular delivery in a rat model of osteoarthritis (OA).Methods. Bindin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
191
1
7

Year Published

2009
2009
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 194 publications
(205 citation statements)
references
References 15 publications
6
191
1
7
Order By: Relevance
“…Lubricin levels in SF decrease after anterior cruciate ligament injury and can take up to a year to return to baseline values (40). Several studies have demonstrated a disease-modifying effect for the intraarticular injection of native or recombinantly expressed lubricin in rodent models of posttraumatic OA (28,29,41,42). Our data indicate that lubricin supplementation likely protects damaged joints by preserving boundary lubrication, thereby protecting articular chondrocytes from apoptosis caused by excessive deformation and shear stress.…”
Section: Discussionmentioning
confidence: 58%
“…Lubricin levels in SF decrease after anterior cruciate ligament injury and can take up to a year to return to baseline values (40). Several studies have demonstrated a disease-modifying effect for the intraarticular injection of native or recombinantly expressed lubricin in rodent models of posttraumatic OA (28,29,41,42). Our data indicate that lubricin supplementation likely protects damaged joints by preserving boundary lubrication, thereby protecting articular chondrocytes from apoptosis caused by excessive deformation and shear stress.…”
Section: Discussionmentioning
confidence: 58%
“…After 13 weeks of treatment, animals were killed and joints were harvested. OA pathology scores were assessed by histologic analysis as described previously (32).…”
Section: Methodsmentioning
confidence: 99%
“…For the latter, the loss starts a cascade of effects including increased friction, increased shear stress across the surface, and ultimately increased cartilage wear and joint degradation. 16 Furthermore, shear stress has been documented with in vitro studies as a negative factor in cartilage failure as a response to injury and extracellular matrix wear. 17,18 Development of a superficial zone damage model through excessive shear would highlight the role of the superficial zone in the progression from healthy cartilage to PTOA.…”
Section: Introductionmentioning
confidence: 99%